PERTANGGUNGJAWABAN PIDANA TERHADAP PENGGUNAAN AUTONOMOUS MEDICAL DEVICE DALAM PELAYANAN KESEHATAN DI INDONESIA - Beni Satria (CV. Lafadz Jaya, 2026)
The advancement of health technology has driven the entry of autonomous medical devices—artificial-intelligence-based medical instruments capable of performing diagnosis, clinical decision-making, and even medical actions with minimal human intervention into healthcare practice in Indonesia. The use of such devices raises new legal issues, particularly concerning the party that may be held criminally liable when a system error or failure causes harm to a patient, given that Indonesia's criminal law system still rests on the principle of fault (mens rea), which can only attach to a legal subject, whether a natural person or a corporation. This study aims to analyze the construction of criminal liability for the use of autonomous medical devices in healthcare services in Indonesia based on Law Number 17 of 2023 on Health together with its implementing regulations, and Law Number 1 of 2023 on the Criminal Code. This study employs a normative juridical method with a statute approach and a conceptual approach, supported by primary, secondary, and tertiary legal materials analyzed in a descriptive-qualitative manner. The findings indicate that autonomous medical devices are not yet recognized as legal subjects, so their position remains that of an object or instrument, and criminal liability for their failure remains attached to medical personnel, healthcare facilities as corporations, and/or device manufacturers, depending on where the fault lies within the chain of the device's use. This study also identifies a legal vacuum in the technical regulation of safety standards, certification, and the proof of algorithmic causation, indicating the need for more specific derivative regulations so that the principles of legal certainty and patient protection can be optimally fulfilled.